Cost-effectiveness of childhood cancer treatment in Egypt: lessons to promote high-value care in a resource-limited setting based on real-world evidence. (January 2023) - Soliman, Ranin; Oke, Jason; Sidhom, Iman; Bhakta, Nickhill; Bolous, Nancy S.; Tarek, Nourhan; Ahmed, Sonia; Abdelrahman, Hany; Moussa, Emad; Zamzam, Manal; Fawzy, Mohamed; Zekri, Wael; et al.
Summary: Background: Childhood cancer in low-and middle-income countries is a global health priority, however, the perception that treatment is unaffordable has potentially led to scarce investment in resources, contributing to inferior survival. In this study, we analysed real-world data about the cost-effectiveness of treating 8886 children with cancer at a large resource-limited paediatric oncology setting in Egypt, between 2013 and 2017, stratified by cancer type, stage/risk, and disease status. Methods: Childhood cancer costs (USD 2019) were calculated from a health-system perspective, and 5-year overall survival was used to represent clinical effectiveness. We estimated cost-effectiveness as the cost per disability-adjusted life-year (cost/DALY) averted, adjusted for utility decrement for late-effect morbidity and mortality. Findings: For all cancers combined, cost/DALY averted was 1384 (0.5 × GDP/capita), which is very cost-effective according to WHO–CHOICE thresholds. Ratio of cost/DALY averted to GDP/capita varied by cancer type/sub-type and disease severity (range: 0.1–1.6), where it was lowest for Hodgkin lymphoma, and retinoblastoma, and highest for high-risk acute leukaemia, and high-risk neuroblastoma. Treatment was cost-effective (ratio <3 × GDP/capita) for all cancer types/subtypes and risk/stage groups, except for relapsed/refractory acute leukaemia, and relapsed/progressive patients with brain tumours, hepatoblastoma, Ewing sarcoma, and neuroblastoma. Treatment cost-effectiveness was affected by the high costs and inferior survival of advanced-stage/high-risk and relapsed/progressive cancers. Interpretation: Childhood cancer treatment is cost-effective in a resource-limited setting in Egypt, except for some relapsed/progressive cancer groups. We present evidence-based recommendations and lessons to promote high-value in care delivery, with implications on practice and policy. Funding: Egypt Cancer Network; NIHR School for Primary Care Research; ALSAC.